The effectiveness use of mind maps in the learning of history / Sabariah Idris and Norfadilah Kamaruddin - Idris, Sabariah; Kamaruddin, Norfadilah (Universiti Teknologi MARA, 2022)
Mind map concept is considered as an effective and meaningful teaching and learning tool previously in many studies. The mind map moreover claimed that it can attract and enhance students' understanding of concepts, information, facts and others. Moreover, mind maps also can be used as self-learning methods that facilitate understanding of difficult concepts. Within the understanding, this study aims to examine the effectiveness of using mind map on learning History subjects for 4th grade students at Sekolah Kebangsaan Seafield, Subang Jaya, Selangor, Malaysia. A visual mind map book was designed to help students to gain more understanding in the study of history. A total of 20 students were taken as a sample of the study and involved in the survey to assess the effectiveness of visual mind map book. As an overall outcome, a visual mind map book contributes to the improvement of students'achievement in the learning of history.